Rural, un territoire pour ralentir ? - Marie Huyghe (Territoire en Mouvement)
According to a recent study led by the Forum Vies Mobiles with 12000 people, 78% of the households surveyed intend to slow down. Rural households share that longing for slowing down, being subject to strong time constraints and injunctions to speed and productivity. Yet, rural households are also subject to territorial constraints which make car use compulsory.Based on the analyses of 75 semi-directive interviews conducted with rural households, we seek to answer the following questions. Which strategies are implemented by the households in order to conciliate all those aspirations, injunctions and constraints? How do they manage to slow down in societies and territories in which speed and car are necessities? Are rural areas suitable, or even favorable, for a slowing down of the households’ pace of life?